Survey and Mapping of Vegetation Density through Remote Sensing and Satellite Imagery - Basuki, Basuki; Romadhon, Muhammad Rizal; Sari, Retno Purnama; Isnanto, Bimo Arvi Aji (University of Jember, 2025)
The development of technology in the current era of globalization is taking place very fast and information technology is needed, among others, as an informant for the situation on the earth's surface. GIS technology can be used to identify vegetation density in an area. The data analysis method used was the NDVI and SAVI vegetation index transformation methods for vegetation density identification. This research was conducted in Ambulu District, Jember Regency, East Java Province. Using satellite images from Landsat 8 OLI imagery which is then explained with descriptive analysis. The identification results showed that for the use of NDVI and SAVI methods, the similarity in the number of classes was 3 classes with low, medium and high categories. It has 3 similarities in classes but there are differences in the area of land in each of these vegetation indexes.